Simulation and understanding of the aerodynamic characteristics of a badminton shuttle - Hart, J. (Procedia Engineering, 2014)
This paper presents a study in the simulation and understanding of the aerodynamic characteristics of a badminton shuttle, using Computational Fluid Dynamics. Modeled shuttle geometry was based upon a high quality synthetic shuttle, a Yonex Mavis 370. The study investigated the use of Reynolds Averaged Navier Stokes (RANS) simulation in comparison to Scale Resolving Simulation (SRS), for the prediction of the complicated flow fields that are associated with the bluff body aerodynamics of badminton shuttles. RANS are known to struggle with predicting large bluff body separations, in comparison to SRS modeling. However SRS modeling can require significant computational resource, and the models require careful application with consideration made to spatial and temporal resolution. It was found that unsteady RANS was capable of predicting comparable time averaged flow field data to the SRS models. Both approaches produced feasible drag coefficient values for the shuttle. However RANS was incapable of predicting the complicated turbulent vortex structures within the shuttle wake, which were captured by SRS.